Screening of chili genotypes against root-knot nematode (Meloidogyne incognita) under screen-house conditions - Kaur, Manjeet; Kumar, Sanjay; Yadav, Saroj; Arora, Indu; Yadav, Bhawna; Kaushik, Prashant (Vegetable Science, 2025)
Chili (Capsicum annuum L.) is a vital crop in global agriculture, particularly in India, where it faces significant challenges from pests, notably root-knot nematodes (RKNs), specifically Meloidogyne incognita. This pathogen significantly impacts both the yield and quality of the crop. To counter these adverse effects, there is a pressing need for resistant genotypes. Consequently, this study was conducted to identify chili genotypes that exhibit resistance to root-knot nematodes, aiming to enhance economic yields. Based on the root-knot index and number of galls, six genotypes (Arka Swetha, Kashi Abha, CIAH/CHES/LPYCHG-2, CIAH/CHES/LPYCHG-3, AICRP-CH 2 and AICRP-CH 3) had shown susceptible reaction with 31.3 to 54.3 number of galls per root system, while 14 genotypes Kashi Anmol, Kashi Ratna, Pusa Sadabahar, CIAH/CHES/LPYCHG-1, CIAH/CHES/LPYCHG-4, CIAH/CHES/LPYCHG-5, CIAH/CHES/LPYCHG-6, CIAH/CHES/LPYCHG-7, CH 1 Raj 2022, CH 2 Raj 2023, AICRP-CH 4, AICRP-CH 5, AICRP-CH 6 and AICRP-CH 7) had shown moderately resistant reaction with 21.0 to 27.0 number of galls per root system and remaining six genotypes (Arka Khyati, Arka Meghana, Arka Harita, CH-RLC 2021, CH-WI 2020 and AICRP-CH 1) had shown resistant reaction with 4.7 to 9.0 number of galls per root system. The resistant genotypes exhibited the least percentage decrease in fresh root weight, fresh shoot weight, dry root weight and dry shoot weight compared to uninoculated plants, whereas the susceptible genotypes showed the greatest reductions. The lowest number of galls per plant, egg masses per root system and reproduction factor were observed in the Arka Harita variety, followed by Arka Meghana. In contrast, the highest values were recorded in Kashi Abha.